KAJIAN TENAGA KERJA PEREMPUAN DALAM BUDIDAYA RUMPUT LAUT (STUDI KASUS DI DESA SERANGAN KECAMATAN DENPASAR SELATAN KOTA DENPASAR) - Handayani, M.Th. (PIRAMIDA; Vol 3, No.1 Juli 2007, 2012)
One indicator of woman role in national development can be seen from an increase of woman participation in working. Eventhough, there is an increase in variety of woman jobs, it does not mean that the woman welfare increases automatically. The woman faces discrimination, not only in domestic sector (non-economy) but also in public sector (economy). Therefore, the study on woman labor analysis was carried out at Serangan village, Denpasar Regency. The study was focused on the woman labor in seaweed (?rumput laut?) culture. The study found that there is a very low income from the seaweed-culture, but the woman income contribute to family income. However woman labor still have a high level of cultural work, the economy activity of woman labor seemed to be just a complementary income in the family. The women labor have not realized yet that their right is supposed to be the same as man labor in the companies farmer. This situation reflects that there is unequal treatment between woman and man labor in the study site, however woman labor still have a high level of cultural work. For this reason, it is recommended that more effective guiden particularly for companies employed many woman labor, should be taken.
Keywords: woman participation, labor in seaweed, family income